Penerapan Model Pembelajaran Koperatif Tipe Picture and Picture Terhadap Hasil Belajar IPA di Sekolah Dasar (IAIN Kendari, 2023)
This classroom action research aims to determine the application of the picture and picture type cooperative learning model and examine the use of the model in improving science learning outcomes in one of the elementary schools in East Kabaena, Southeast Sulawesi. The results of quantitative and qualitative data analysis show that the form of learning the picture and picture model in this school is carried out by utilizing images in which there are activities to install or sort images into a logical sequence. The activity of teachers and students in learning has shown a good improvement from cycle to cycle. Teachers find it easier to manage classes and focus students on the learning process, while students are more enthusiastic about learning, confident in asking questions and doing percentages in front of the class. The application of picture and picture type cooperative learning models is proven to help students in improving learning outcomes.Keywords: Picture and picture model learning, cooperative learning, learning outcome of science